Safety and efficacy of hematopoietic and mesanchymal stem cell therapy for treatment of T1DM: a systematic review and meta-analysis protocol - Sedigheh Madani; Bagher Larijani; Abbas Ali Keshtkar; Ali Tootee (Systematic Reviews, 2018)
Abstract Introduction Insulin standard treatment of T1DM cannot cure the patients as different chronic complications occurred subsequently. Investigations on a curative treatment in T1DM propose cell replacement or maintenance instead of exogenous insulin therapy, but different dimensions of this novel treatment are not clarified. Methods and analysis We will include all clinical trials which have evaluated the efficacy MSC or HSC transplantation in T1DM treatment; electronically search bibliographic databases, country registration data banks, and gray literatures; and hand-search two key journals, two experts’ article, and references of the included articles with no language restriction. Primary outcome is the extent of reduction in insulin requirement and secondary outcomes are safety of MSC and HSC therapy, effect of this therapy on diabetic parameters, effect of the rout of transplantation and origin of the MSC or HSC on efficacy of treatment, studies heterogeneity and potential reasons of it. Heterogeneity and its severity will be calculated with Q Cochrane test, P value, and I 2 index. STATA software version 12 will be used for meta-analysis. PROSPERO Registration number: CRD42016047176. Ethics and dissemination We will publish the systematic review in a peer review journal; as it presents an analysis of published literature, the study does not require ethical approval. Strengths and limitations of this study This systematic review and meta-analysis will investigate the efficacy of MSC and HSC transplantation in T1DM treatment with no language restriction. Also we will evaluate gray literatures after hand searching. This protocol is prepared according to Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Two reviewers will evaluate screened full texts, extract data, and asses risk of bias of eligible primary studies independently. As there is the possibility that we miss some unpublished primary studies due to negative results, we will use funnel plot to detect this and correct it with fill and trim method.